Analisis Pengaruh Penambahan Belerang Terhadap Kuat Geser Tanah - Farhan, Erham Muhammad; Azizi, Amris; Afriandiny, Besty (Proceedings Series on Physical & Formal Sciences, 2023)
Stable soil is needed in a construction development. There are many ways and materials that can be used to improve soil properties that are less stable. Sulfur as one of the natural products in Indonesia has not been used optimally in the field of civil engineering, especially geotechnical engineering. Therefore, in-depth research is needed regarding the benefits of this sulfur in the world of civil engineering. The purpose of this study was to find out how the effect of mixing sulfur on the shear strength of the soil in the direct shear strength test and to find out at what ratio the sulfur mixture produced the greatest soil shear strength. This research was conducted on chemically stabilized soil samples in the form of addition of sulfur with various mixture variations. The results showed that the addition of sulfur at the percentage of 2%, 3% and 5% increased the cohesion value of the soil compared to the original soil. The addition of sulfur with a percentage of 6% and 7% decreases the soil cohesion value. The greatest increase in soil cohesion occurred in the 2% mixture with an increase of 86.95%. The percentage of 2% increases the value of the largest soil shear strength which is equal to 52.953 kPa from the original soil shear strength value of 48.716 kPa.